2016
DOI: 10.1002/slct.201600926
|View full text |Cite
|
Sign up to set email alerts
|

Pine Wood Extracted Activated Carbon through Self‐Activation Process for High‐Performance Lithium‐Ion Battery

Abstract: Self-activation is an ecological friendly and inexpensive process for the fabrication of large scale activated carbon (AC), which precludes the use of activating agents and takes advantage of the emitted gases from the simple pyrolysis of pine wood to stimulate the converted carbon. The tailoring of process parameters such as dwelling time assists in optimizing the pore size distribution comprised of meso-and micropores, offering favorable physical properties including specific surface area of 2738 m 2 g À1 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…Indeed, the composition of the precursor enables the self-activation (chemical or physical) during the thermal degradation of the matrix. For example, highly porous carbons have been obtained by carbonization of organic polymers, biopolymers and their salts (i.e., gluconates, alginates, citrates, sulfonates, maleic acid), and biomass containing alkaline or alkali earth elements as precursors [69][70][71][72][73][74][75][76][77][78][79][80][81][82][83]. These compounds combine a carbon precursor and certain elements that during the heat-treatment generate species capable of acting as activating agents (releasing CO 2 , K, Na, etc.…”
Section: Self-activationmentioning
confidence: 99%
“…Indeed, the composition of the precursor enables the self-activation (chemical or physical) during the thermal degradation of the matrix. For example, highly porous carbons have been obtained by carbonization of organic polymers, biopolymers and their salts (i.e., gluconates, alginates, citrates, sulfonates, maleic acid), and biomass containing alkaline or alkali earth elements as precursors [69][70][71][72][73][74][75][76][77][78][79][80][81][82][83]. These compounds combine a carbon precursor and certain elements that during the heat-treatment generate species capable of acting as activating agents (releasing CO 2 , K, Na, etc.…”
Section: Self-activationmentioning
confidence: 99%
“…By simulating the storage of solvents and sodium ions in the electrode material, Karatrantos [52] found that electrolyte ions existe in pores larger than 0.85 nm. It is shown that with surface charges applied to the two innermost graphene sheets, Na + ions enter the subnanometer pores; as the surface charge of [109] Copyright 2009, De Gruyter (b)illustration of self-activation of biomass using self-emitted gases, and the effect of pore size variation with activating time; [110] Copyright 2016, Wiley (c) the pore size distribution, showing the porosity difference among different samples; (d) the comparison of rate performance; [111] Copyright 2019, American Chemical Society. (e) pore size distribution and (f) rate performance of NPDC; [112] Copyright 2021, Elsevier.…”
Section: Constructed Porous Structure Of Plant-based Hard Carbonmentioning
confidence: 99%
“…Figure9. (a) Schematic cross-section of a porous solid;[109] Copyright 2009, De Gruyter (b)illustration of self-activation of biomass using self-emitted gases, and the effect of pore size variation with activating time;[110] Copyright 2016, Wiley (c) the pore size distribution, showing the porosity difference among different samples; (d) the comparison of rate performance;[111] Copyright 2019, American Chemical Society. (e) pore size distribution and (f) rate performance of NPDC;[112] Copyright 2021, Elsevier.…”
mentioning
confidence: 99%
“…6b). 118 When served as an anode for LIBs, the carbon electrode achieves a stable capacity of 700 mA h g −1 at 0.2 C. Researchers are able to a develop sustainable and high-performance anode for LIBs by benefiting from the natural features of wood. Chen et al 119 developed an in situ sacrificial template-assisted hydrothermal approach that utilized graphitic carbon nitride as both a template and a nitrogen source to produce nitrogen-doped porous carbon fiber using wood fiber as raw material (Fig.…”
Section: Green Carbon Resources For Carbon Anodesmentioning
confidence: 99%